2004
DOI: 10.1046/j.0305-0270.2003.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding bird species richness in Taiwan: distribution on gradients of elevation, primary productivity and urbanization

Abstract: Aim  To examine the richness of breeding bird species in relation to elevation, primary productivity and urbanization. Location  The island of Taiwan (120°–122° E, 22°–25° N). Methods  We arranged bird species richness (BSR) data from 288 bird censuses undertaken in Taiwan into a 2 × 2 km quadrat system and calculated average values of elevation, primary productivity [surrogated by normalized difference vegetation index (NDVI)], and urbanization (surrogated by road density and percentage of built area) for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 48 publications
(55 reference statements)
6
82
2
1
Order By: Relevance
“…The pattern of the avian community of the present study varies from that reported by many previous studies conducted on bird species richness along altitudinal gradients mostly in temperate regions. Most such studies have found the highest species richness at low elevation such as in rain forest of eastern Andes Peru (Terborgh 1971;Terborgh & Weske 1975) or mid elevation such as in Peruvian Andes (Rahbek 1995(Rahbek , 2005, Madagascan rain forest (Colwell & Lees 2000), Bolwian Andes South American Forest (Kessler et al 2001), Columbian Andes forest (Kattan & Franco 2004), urban/subtropical to subarctic forest in Taiwan (Lee et al 2004;Ding et al 2005). In the present study the higher BSD and BSR observed in high altitude areas may be connected to the higher plant diversity.…”
Section: Discussionmentioning
confidence: 49%
“…The pattern of the avian community of the present study varies from that reported by many previous studies conducted on bird species richness along altitudinal gradients mostly in temperate regions. Most such studies have found the highest species richness at low elevation such as in rain forest of eastern Andes Peru (Terborgh 1971;Terborgh & Weske 1975) or mid elevation such as in Peruvian Andes (Rahbek 1995(Rahbek , 2005, Madagascan rain forest (Colwell & Lees 2000), Bolwian Andes South American Forest (Kessler et al 2001), Columbian Andes forest (Kattan & Franco 2004), urban/subtropical to subarctic forest in Taiwan (Lee et al 2004;Ding et al 2005). In the present study the higher BSD and BSR observed in high altitude areas may be connected to the higher plant diversity.…”
Section: Discussionmentioning
confidence: 49%
“…The elevational gradient has traditionally been used as a substitute for productivity, with the assumption that at higher elevation the environmental conditions contribute to lower productivity (MacArthur 1969, Terborgh 1971, Navarro 1992, Lee et al 2004, Rahbek 2005. In fact, in RPSP, the more complex and productive habitats are in the lower part of the PA, where there are riparian forests along the Preto River (and other streams) and savannah areas with denser vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the covariates studied vary across Taiwan in tandem with elevation (Lee et al, 2004): high elevation areas are less accessible and more difficult to cultivate, leading to lower population densities, higher NDVI values, lower socioeconomic status and differences in land cover and land use patterns. In addition, temperatures are lower and rainfall higher in high elevation areas.…”
Section: Discussionmentioning
confidence: 99%